Numerical algorithms for personalized search in self-organizing information networks - Kamvar, Sep 1977- (Princeton, N.J. Princeton University Press, 2010)
"This book lays out the theoretical groundwork for personalized search and reputation management, both on the Web and in peer-to-peer and social networks." The book develops scalable algorithms that exploit the graphlike properties underlying personalized search and reputation management, and delves into realistic scenarios regarding web-scale data.--[book cover]
World Wide Web -- PageRank -- The second eigenvalue of the Google Matrix -- The condition number of the pagerank problem -- Extrapolation algorithms -- Adaptive pagerank -- BlockRank -- P2P networks. Query-cycle simulator -- EigenTrust -- Adaptive P2P topologies.
Keywords: Database searching -- Mathematics; Information networks -- Mathematics; Content analysis (Communication) -- Mathematics; Self-organizing systems -- Data processing; Algorithms; Internet searching -- Mathematics